2011
DOI: 10.1590/s1517-83822011000100045
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of a mixture of biosurfactant from Bacillus subtilis and alkaline lipase from Fusarium oxysporum

Abstract: In this study, we investigate the antimicrobial effects of a mixture of a biosurfactant from Bacillus subtilis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 23 publications
0
4
0
1
Order By: Relevance
“…They could be produced from renewable resources (micro-organisms, plants and animal oils) and petrochemical feedstock [1] as well as reduced surface tension in both aqueous and hydrocarbon [2]. Biosurfactants possess many advantages such as selectivity, diversity, appropriate for large-scale production and environment-friendly nature over their chemically synthesized counterparts [3]. Amani et al [4]; Singh et al [5]; Kruijt et al [6], reported a considerable number of rhizosphere and plant associated microbes involved in biosurfactant production and their application in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…They could be produced from renewable resources (micro-organisms, plants and animal oils) and petrochemical feedstock [1] as well as reduced surface tension in both aqueous and hydrocarbon [2]. Biosurfactants possess many advantages such as selectivity, diversity, appropriate for large-scale production and environment-friendly nature over their chemically synthesized counterparts [3]. Amani et al [4]; Singh et al [5]; Kruijt et al [6], reported a considerable number of rhizosphere and plant associated microbes involved in biosurfactant production and their application in agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Although the ideal condition for biosurfactant production is a medium like MSSO, Bacillus can still produce biosurfactants in the BHI medium, as reported previously 75 . Moreover, numerous studies have employed BHI as an effective medium for biosurfactant production by different bacteria types [76][77][78][79] . In previous investigations, BHI was proven to be effective in cultivating G. Stearothermophilus under harsh conditions 13,69,71,72 .…”
Section: Cultivation Of Bacteriamentioning
confidence: 99%
“…Useful microorganisms from the rhizo- and phyllospheres are capable of synthesizing complex active BAS, including antibiotics of various chemical classes, enzymes and metabolites with signaling and hormonal functions [ 81 , 82 , 83 , 84 ]. Auxins, gibberellins, cytokin-ins, abscisic (ABA), salicylic and jasmonic acids synthesized by microbial strains are found to be natural growth regulators [ 85 , 86 ].…”
Section: Discussionmentioning
confidence: 99%